2016
DOI: 10.1111/jeu.12289
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the Highly Divergent Echinosteliales (Amoebozoa)

Abstract: Myxomycetes or plasmodial slime molds are widespread and very common soil amoebae with the ability to form macroscopic fruiting bodies. Even if their phylogenetic position as a monophyletic group in Amoebozoa is well established, their internal relationships are still not entirely resolved. At the base of the most intensively studied dark-spored clade lies the order Echinosteliales, whose highly divergent small subunit ribosomal (18S) RNA genes represent a challenge for phylogenetic reconstructions. This is be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
2
15
2
Order By: Relevance
“…; Kretzschmar et al. ). Physarida is characterized by the presence of lime (calcareous deposits), whose structure, either crystalline or amorphous, and its localization in different parts of the sporophore are used to distinguish the two families, Didymiidae (Didymiaceae according to the botanical code) and Physaridae (Physaraceae) (Poulain et al.…”
Section: Specimens Used In This Study Herbarium Number Location Comentioning
confidence: 98%
See 1 more Smart Citation
“…; Kretzschmar et al. ). Physarida is characterized by the presence of lime (calcareous deposits), whose structure, either crystalline or amorphous, and its localization in different parts of the sporophore are used to distinguish the two families, Didymiidae (Didymiaceae according to the botanical code) and Physaridae (Physaraceae) (Poulain et al.…”
Section: Specimens Used In This Study Herbarium Number Location Comentioning
confidence: 98%
“…2010b, ; Kretzschmar et al. ). The Fuscisporidia include three orders, the basal, paraphyletic Echinosteliida, and Stemonitida paraphyletic to the monophyletic Physarida (Fiore‐Donno et al.…”
Section: Specimens Used In This Study Herbarium Number Location Comentioning
confidence: 99%
“…However, both of the two types were reported in the Physarales (Chen et al 2013;Ishibashi et al 2001;Lado et al 2007;Liu et al 2010;Song et al 2014;Wrigley de Basanta et al 2008, 2011. Phylogenetic relationships confirmed that Columellidia is composed of the paraphyletic Stemonitales and the monophyletic Physarales, with Echinosteliales as a sister group of both (Fiore-Donno et al 2009;Kretzschmar et al 2015). Thus, it indicated the V-shape split germination, appearing in Didymiaceae and Physaraceae, may be an evolutionary character.…”
Section: Discussionmentioning
confidence: 90%
“…In the traditional classification, there are five orders in the plasmodial slime molds, including Echinosteliales, Liceales, Trichiales, Physarales and Stemonitales (Martin et al 1983). This group is confirmed as a firmly established clade in Amoebozoa by the elevated molecular data and is subdivided into dark-spored clade (Echinosteliales, Stemonitales, and Physarales) and bright-spored clade (Liceales and Trichiales), the two clades were called Columellidia and Lucisporidia, respectively (Cavalier-Smith 2013;Fiore-Donno et al 2009;Fiore-Donno et al 2013;Kretzschmar et al 2015;Shadwick et al 2009).…”
mentioning
confidence: 73%
See 1 more Smart Citation